THORACIC SURGERY IN EQUINES - M. Jawad, N. (The Iraqi Journal of Veterinary Medicine, 1987)
Unilateral. thoracotomy was performed in twenty nine donkeys and twenty five horses aged 4-10 years without an ‘aid of positive ‘respirator. Surgical pneumothorax did not endanger the life of patient. Eighteen horses and twenty four donkeys became clinically “normal and the wounds were completely healed within 30 days, however, two horses .dies due to pleurisy. Five horses and five donkeys were killed and subjected to anatomical studies to find out if .there is a communication between the plural sacs or if the mediastinum is not strong enough to resist pressure. Observations indicate that there is no communication between the two plural sacs and that the mediastinum is strong enough to resist the difference in the pressure of the plural sacs and thus permit open thoracic surgery in equine without employing inflating pump.